Multiperspectivity in organized sport in refugee sites: Sociological findings and pedagogical considerations - Michelini, Enrico; Schreiner, Laura (Frontiers in Sports and Active Living, 2022)
Refugee sites are a means to manage large-scale refugee movements, a recurring event in today's world. Sport is supposed to have beneficial effects for the residents of such sites and is therefore an activity, which is standardly organized by the sites' management. Moreover, many NGOs and “Sport for Development and Peace” programmes endorse the use of sport in emergency situations—including in refugee sites—to achieve several biopsychosocial objectives. There is a growing body of scientific literature, however, that is calling into question the beneficial effects of sport in this setting as well as the rationale behind this idea. Against this background, we explore the question “How does multiperspectivity influence sport in refugee sites?” based on two case studies. We use the ethnographic materials we were able to collect for the case studies to conduct a (sociological) analysis of multiperspectivity in sport and to develop (pedagogical) proposals on how to incorporate multiperspectivity when devising sports activities for refugees. The fact that the perspectives and motivations beyond the actual sports activities in the refugee site setting might be extremely homogenous leads us to conclude that multiperspectivity is key for planning, organizing and monitoring sports activities, and that refugees' positions must also be acknowledged. We recommend programmes and practical ways of achieving these objectives with a focus on the role of trainers and coaches.